Hydrogeological Characterization of Crystalline Bedrock Using Borehole Magnetic Resonance - Eeva, Salla Talvikki; Karjalainen, Aino Iida Elina; Koivisto, Emilia; Korkka-Niemi, Kirsti; Rautio, Anne Brita Kristina; Räisänen, Olli; Gee, Ryan; Birt, Benjamin (Wiley Blackwell, 2024)
We aimed to test borehole magnetic resonance (BMR) method for determining hydraulic parameters (porosity, permeability, and hydraulic conductivity) required for hydrogeological modeling in two distinct crystalline rock environments. These sites comprise Proterozoic basement rocks of different compositions: mafic rocks at the Sakatti mining development site in northern Finland and felsic rocks at the Olkiluoto Island nuclear repository site in southwest Finland. Although BMR is widely used for determining storage and hydraulic properties in sedimentary environments, there have been few studies in crystalline bedrocks. The results indicate that BMR is a suitable tool for studying lithologically and hydrogeologically heterogeneous fractured crystalline bedrocks. It can produce continuous data from hydraulic properties of bedrock in addition to more time-consuming methods such as flowmeter and packer tests and can provide guidance on where to focus additional flow measurements. The intervals display fracture and reduced matrix porosity characteristics, both of which can be enhanced or reduced locally by chemical alteration and by tectonic processes. Flow parameters vary significantly throughout the studied intervals: independently from the lithological composition, these intervals locally display relatively high porosities, and may be correlated to the more intensely fractured and/or brecciated zones. However, due to the heterogeneity in mineralogy, grain/pore arrangement, and the variability of fracture flow-driven transport in each borehole, the challenge remains in finding a unique set of permeability constants for these crystalline rock types. The permeability models could be calibrated by laboratory measurements of the core, and possibly a new permeability model suitable for crystalline bedrock could be created. Peer reviewed